Patient satisfaction and outcomes of static progressive stretch bracing: a 10-year prospective analysis - Sodhi, Nipun; Yao, Benjamin; Anis, Hiba K.; Khlopas, Anton; Sultan, Assem A.; Newman, Jared M.; Mont, Michael A. (Annals of Translational Medicine; Vol 7, No 4 (February 27, 2019): Annals of Translational Medicine (Focus on “Lower Extremity Arthroplasty”), 2018)
Background: Multiple surgical and non-surgical modalities are available for patients suffering from shoulder elbow, forearm, wrist, knee and ankle stiffness. For most patients, bracing can provide optimal therapy to restore functional range of motion (ROM). Three commonly used bracing mechanisms include static progressive stretch (SPS), turnbuckle, and dynamic bracing. However, although, in general, these three brace types have been shown to have successful outcomes, there are a number of different manufacturers, and company specific designs might affect outcomes. Therefore, the purpose of this study was to analyze 10 years of prospectively collected patient satisfaction and outcomes data from a single brace company. Specifically, we evaluated: (I) mobility, (II) pain, (III) stiffness, (IV) swelling, and (V) any adverse events of patients treated with an SPS brace. Methods: From 2007 to 2017, data from a total of 167,751 patients treated with a JAS Brace (Joint Active Systems Inc., Effingham, IL, USA) were prospectively collected through a cross-sectional survey addressing various outcomes such as pain, stiffness, swelling and mobility. More specifically, patients were asked “Are you having pain?”, “Do you have any stiffness?”, “Do you have any swelling?”, and “Do you feel your mobility has improved?” Patients who answered “yes” were then asked to categorize their response as either worse, same, or better (or improvement) for pain, stiffness, and swelling. For mobility, patients answered either “yes”, “no”, or “undecided”. This data was then graphed and a yearly trends analysis was performed. We also assessed the number of complaints as well as any device related adverse events. Results: In 2008, 59% of patients reported no pain, 45% no stiffness, and 79% no swelling after device use. Those numbers increased by 2013, to 70% of patients reporting no pain, 79% reporting no stiffness, and 84% reporting no swelling after brace use. A consistent positive trend was also seen for mobility, with at least 90% of patients reporting improved mobility after orthosis use. The number of complaints decreased from 38 in 2007 to 3 in 2017. No patients experienced any device related serious injuries. Conclusions: Overall, to the best of the author’s knowledge, this study is the first to demonstrate a brace designed to improve ROM also has significant effect on pain, stiffness, and swelling. These results are of particular importance, since no other study reports prospective data on thousands of patients showing that a bracing system substantially reduces pain and stiffness. These data indicate that not only or these SPS braces effective in improving functional ROM with high rate of success and no significant complications, but this bracing system has a significant effect on improving pain and stiffness. Based on the results from this study, patients suffering from shoulder, elbow, forearm, wrist, knee and/or ankle pathology can expect excellent clinical outcomes by using one of the above braces.